Enhancing The Students’ Speaking Skill through Think-Pair-Share (TPS) at SMAN 4 Jember - Muhammad 'Abduh Al Karim; Mutiara Bilqis; Bambang Suharjito (EFL Education Journal, 2022)
This research discussed about using think-pair-share (TPS) at the state senior high school in the online teaching and learning process during the covid-19 pandemic. This research aims To enhance the eleventh-grade students’ speaking skill and participation at state senior high school 4 Jember by using Think–Pair-Share (TPS). The design of this research is a Classroom Action Research (CAR) with thirty participants in the classroom to collect the data. The teacher said that the eleventh grade students had difficulties in speaking skill. They felt unconfident to speak. This problem made their speech less fluent. They also often pronounced the English words incorrectly and displayed grammar errors when speaking. Students’ participation in the learning process was low because they felt unconfident and afraid of expressing their ideas in oral speech. Kagan (1994) said that TPS is a cooperative learning strategy that can promote higher-level thinking. TPS has useful benefits, not only for the students but also for the teacher. The students are allowed to speak up in the class. They talk a lot in the class, have high motivation in speaking, and enjoy participating in the class is the characteristic of successful speaking activities. The findings of this study, it proved that Think-Pair-Share (TPS) strategy could enhance the students’ speaking skill at SMAN 4 Jember. It could be seen from the improvement of the students’ speaking test result in the first cycle. It happened because the students were encouraged to speak English by the pair and have a discussion in class. It creates positive atmosphere in sharing ideas about the material and the students can train their vocabularies and pronunciation.